Secondary battery and electronic device

The secondary battery design, featuring a negative electrode with silicon carbon composite particles and a specific electrolyte composition, enhances energy density and cycle resistance, overcoming the limitations of silicon-based batteries.

JP2025069258AActive Publication Date: 2025-04-30NINGDE AMPEREX TECHNOLOGY LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2025012340
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-05-10
Filing Date
2025-01-28
Publication Date
2025-04-30
Estimated Expiration
2045-01-28

AI Technical Summary

Technical Problem

Secondary batteries using silicon materials face challenges with energy density limitations and deterioration of electrochemical performance due to large expansion and contraction during ion storage and release.

Method used

A secondary battery design incorporating a negative electrode with a mixture layer containing silicon carbon composite particles and a conductive agent, optimized with specific particle size and composition ratios, along with an electrolyte comprising propylene carbonate and ethylene carbonate, to enhance energy density and cycle resistance.

Benefits of technology

The solution achieves high energy density and improves the rate of increase in high temperature cycle resistance and rapid charging cycle resistance, effectively addressing the performance limitations of silicon-based secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069258000001
    Figure 2025069258000001
  • Figure 2025069258000002
    Figure 2025069258000002
  • Figure 2025069258000003
    Figure 2025069258000003
Patent Text Reader

Abstract

To provide a secondary battery in which high energy density is achieved while the high-temperature cycle resistance growth rate and the fast-charge cycle resistance growth rate are both improved.SOLUTION: A secondary battery includes a negative electrode, a positive electrode, and an electrolyte. The negative electrode includes a negative electrode current collector and a negative electrode mixture layer arranged on at least one surface of the negative electrode current collector. The negative electrode mixture layer contains a conductive agent and silicon-carbon composite particles. The average particle size of the silicon-carbon composite particles is D μm. The silicon-carbon composite particles contain silicon elements and carbon elements. When the mass percentage of the silicon element is C% based on the sum of masses of the silicon elements and the carbon elements, C and D satisfy 0.21≤C / D2≤1.2. The electrolyte contains propylene carbonate and ethylene carbonate, and, when the sum of the mass percentages of the propylene carbonate and the ethylene carbonate is H% based on the mass of the electrolyte, H satisfies 15≤H≤50.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of energy storage, specifically to secondary batteries and electronic devices. [Background technology]

[0002] As a means of energy storage and energy supply, secondary batteries are an important option for meeting the demands of sustainable development. With the expansion of their application fields, the demand for secondary battery energy density is also increasing. Graphite materials are widely used as traditional negative electrode materials, but their theoretical capacity is limited. In contrast, silicon materials have a higher theoretical capacity, are abundant in source and inexpensive, and have the potential to become the next generation of secondary battery materials. However, silicon materials undergo large expansion and contraction during the process of absorbing and releasing metal ions, which leads to deterioration of electrochemical performance. Therefore, in order to ensure the widespread application of silicon materials, it is necessary to increase the energy density and avoid deterioration of other electrochemical performance of secondary batteries. Summary of the Invention

[0003] An object of the present invention is to provide a secondary battery and an electronic device that achieve a high energy density while simultaneously improving the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate.

[0004] In a first aspect, the present invention provides a secondary battery and an electronic device. The secondary battery includes a negative electrode, a positive electrode, and an electrolyte, the negative electrode includes a negative electrode current collector and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector, the negative electrode mixture layer includes a conductive agent and silicon carbon composite particles, the silicon carbon composite particles have an average particle size of D μm, the silicon carbon composite particles include elemental silicon and elemental carbon, and when the mass percentage of elemental silicon is C % based on the total mass of elemental silicon and elemental carbon, C and D satisfy the following relationship: 0.21≦C / D 2≦1.2. The electrolyte contains propylene carbonate and ethylene carbonate, and when the total mass percentage of propylene carbonate and ethylene carbonate is H% based on the mass of the electrolyte, H satisfies 15≦H≦50. The secondary battery provided by the present invention achieves a high energy density while simultaneously improving the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate.

[0005] The inventors found that the resistivity of a secondary battery containing silicon-carbon composite particles increases significantly after cycling. Such deterioration of characteristics is particularly noticeable after high-temperature cycles and rapid charging cycles. By setting the secondary battery as described above, it is possible to achieve a high energy density and improve both the high-temperature cycle resistance increase rate and the rapid charging cycle resistance increase rate. The inventors speculate that in the process of occlusion and release of metal ions, the volume of the silicon-carbon composite particles expands and contracts significantly, and the conductive agent is displaced with the expansion of the silicon-carbon composite particles, but the displacement of the conductive agent cannot be fully restored with the contraction of the silicon-carbon particles, resulting in the conductive network inside the negative electrode being cut off. In the process of high-temperature cycles and rapid charging cycles, the degree of expansion and contraction of the volume of the silicon-carbon composite particles is greater, and the rate of expansion and contraction is also faster, so that the conductive network inside the negative electrode is more easily cut off, and the resistivity of the secondary battery increases significantly after high-temperature cycles and rapid charging cycles. The average particle size Dμm of the silicon carbon composite particles affects the stacking form of the silicon carbon composite particles inside the negative electrode, and further affects the distribution state and displaceable space of the conductive agent inside the negative electrode, and the mass percentage C% of silicon element affects the degree and speed of expansion and contraction of the silicon carbon composite particle volume. The average particle size Dμm of the silicon carbon composite particles and the mass percentage C% of silicon element are 0.21≦C / D 2By controlling the ratio H% to satisfy 15≦H≦50, the secondary battery can achieve a high energy density and simultaneously improve the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate. In addition, by controlling the ratio H% to satisfy 15≦H≦50, the quality of the solid electrolyte interfacial film formed on the surface of the silicon carbon composite particles can be optimized, the connection between the silicon carbon composite particles and the conductive agent can be strengthened, and the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved.

[0006] In some embodiments, C and D are greater than or equal to 0.39 C / D 2 Meets ≦0.96. C / D 2 By adjusting the value of within the above range, the trade-off relationship between the displaceable space of the conductive agent and the degree and speed of expansion and contraction of the silicon carbon composite particle volume can be further adjusted, and the high temperature cycle resistance increase rate and the fast charging cycle resistance increase rate can be further improved.

[0007] In some embodiments, C and D are greater than or equal to 0.58 C / D 2 Meets ≦0.88. C / D 2 By adjusting the value of within the above range, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0008] In some embodiments, D satisfies 7.1≦D≦10.9, and C satisfies 25≦C≦59. By adjusting the value of D and / or C within the above range, the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate can be further improved.

[0009] In some embodiments, the electrolyte contains propyl propionate and ethyl propionate, and when the total mass percentage of propyl propionate and ethyl propionate based on the mass of the electrolyte is L%, L and / or H satisfy 12≦L≦39 and 18≦H≦44. By adjusting the value of L and / or H within the above range, the thickness and composition of the solid electrolyte interfacial film on the surface of the silicon carbon composite particles can be adjusted to strengthen the connection between the silicon carbon composite particles and the conductive agent, further reducing the possibility of the conductive network being blocked inside the negative electrode, and improving the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate.

[0010] In some embodiments, the electrolyte satisfies at least one of (1) 18≦L≦34 and (2) 24≦H≦39. By adjusting the value of L and / or H within the above range, the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate can be further improved.

[0011] In some embodiments, when the mass percentage of propyl propionate is L1% and the mass percentage of ethyl propionate is L2%, L1 and L2 satisfy 1.3≦L1 / L2≦2.8. By adjusting the value of L1 / L2 within the above range, the uniformity of the solid electrolyte interfacial film can be improved, the connection between the silicon carbon composite particles and the conductive agent can be strengthened, the possibility of the conductive network being blocked inside the negative electrode can be further reduced, and the high temperature cycle resistance increase rate and the fast charging cycle resistance increase rate can be further improved. Optionally, L1 and L2 satisfy 1.7≦L1 / L2≦2.3.

[0012] In some embodiments, when the mass percentage of propylene carbonate is H1% and the mass percentage of ethylene carbonate is H2%, H1 and H2 satisfy 0.9≦H1 / H2≦2.3. By adjusting the value of H1 / H2 within the above range, the uniformity of the solid electrolyte interfacial film can be improved, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved. Optionally, H1 and H2 satisfy 1.1≦H1 / H2≦2.0.

[0013] In some embodiments, the electrolyte contains 1,3-propane sultone, and when the mass percentage of 1,3-propane sultone is P% based on the mass of the electrolyte, P satisfies 2.6≦P≦4.7. By adjusting the value of P within the above range, the elasticity of the solid electrolyte interfacial membrane and the ability to connect the conductive agent can be improved, the possibility of irreversible displacement occurring during the process of the conductive agent silicon carbon composite particle volume expansion and contraction can be reduced, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved. Optionally, 3.1≦P≦4.2.

[0014] In some embodiments, the electrolyte contains at least one of fluorobenzene, fluoroethylene carbonate, and lithium difluorophosphate, and the electrolyte satisfies at least one of the following, based on the mass of the electrolyte: (1) when the mass percentage of fluorobenzene is F1%, F1 satisfies 1.1≦F1≦4.3; (2) when the mass percentage of fluoroethylene carbonate is F2%, F2 satisfies 10.3≦F2≦19.8; and (3) when the mass percentage of lithium difluorophosphate is F3%, F3 satisfies 0.01≦F3≦0.32. By making the electrolyte satisfy at least one of the above, the elasticity of the solid electrolyte interfacial film and the ability to connect the conductive agent can be improved, the possibility of the conductive network being blocked inside the negative electrode can be further reduced, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0015] In some embodiments, the electrolyte contains dimethyl sulfone, and when the mass percentage of dimethyl sulfone is S% based on the mass of the electrolyte, S satisfies 1.1≦S≦3.4. By adjusting the value of S within the above range, the elasticity of the solid electrolyte interfacial film and its ability to adsorb the conductive agent can be improved, the possibility of irreversible displacement occurring during the process of the volume expansion and contraction of the silicon carbon composite particles of the conductive agent can be reduced, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0016] In some embodiments, the electrolyte contains 1,4-dioxane, and when the mass percentage of 1,4-dioxane is W% based on the mass of the electrolyte, W satisfies 2.3≦W≦4.6. By adjusting the value of W within the above range, the elasticity of the solid electrolyte interfacial film and its ability to adsorb the conductive agent can be improved, the connection strength between the silicon carbon composite particles and the conductive agent can be enhanced, and the high temperature cycle resistance increase rate and the fast charging cycle resistance increase rate can be further improved.

[0017] In some embodiments, C and F1 are such that 3.4≦C / F1 2 Meets ≦13.8. C / F1 2 By adjusting the value of within the above range, the trade-off relationship between the elasticity of the solid electrolyte interfacial film and the degree and speed of expansion and contraction of the silicon carbon composite particle volume can be further adjusted, the connection strength between the silicon carbon composite particle and the conductive agent can be improved, and the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate can be further improved.

[0018] In some embodiments, the silicon carbon composite particles comprise a carbon skeleton and a protective layer located on a surface of at least a portion of the carbon skeleton, wherein the material of the protective layer comprises amorphous carbon and the material of the carbon skeleton comprises at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, and hard carbon.

[0019] In some embodiments, the conductive agent comprises carbon nanotubes. By using a conductive agent comprising carbon nanotubes, the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate can be further improved.

[0020] A second aspect of the present invention provides an electronic device including the secondary battery provided by the first aspect of the present invention. The secondary battery provided by the second aspect of the present invention achieves high energy density while simultaneously improving the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate.

[0021] Additional aspects and advantages of embodiments of the invention will be set forth in part in the description that follows, or will be illustrated by, or may be learned by, the practice of embodiments of the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Examples of the present invention will be described in detail below. The examples of the present invention should not be construed as limiting the present invention.

[0023] Unless otherwise stated, the following terms used herein have the meanings indicated below.

[0024] In a first aspect, the present invention provides a secondary battery and an electronic device. The secondary battery includes a negative electrode, a positive electrode, and an electrolyte, the negative electrode includes a negative electrode current collector and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector, the negative electrode mixture layer includes a conductive agent and silicon carbon composite particles, the silicon carbon composite particles have an average particle size of D μm, the silicon carbon composite particles include elemental silicon and elemental carbon, and when the mass percentage of elemental silicon is C % based on the total mass of elemental silicon and elemental carbon, C and D satisfy the following relationship: 0.21≦C / D 2≦1.2. The electrolyte contains propylene carbonate and ethylene carbonate, and when the total mass percentage of propylene carbonate and ethylene carbonate is H% based on the mass of the electrolyte, H satisfies 15≦H≦50. The secondary battery provided by the present invention achieves a high energy density while simultaneously improving the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate.

[0025] negative electrode The negative electrode includes a negative electrode current collector and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector, the negative electrode mixture layer including a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent unintentional deposition of the active material (e.g., lithium metal) on the negative electrode during charging.

[0026] The negative electrode active material includes silicon carbon composite particles. In some embodiments, C and D are 0.21≦C / D 2 In some embodiments, C and D satisfy the following relationship: 0.21≦C / D 2 In some embodiments, C and D satisfy the following relationship: 0.39≦C / D≦1.17. 2 In some embodiments, C and D satisfy the following: 0.39≦C / D 2 In some more preferred embodiments, C and D satisfy the following relationship: 0.39≦C / D 2 In some more preferred embodiments, C and D satisfy the following relationship: 0.39≦C / D 2 In some more preferred embodiments, C and D satisfy the following relationship: 0.58≦C / D 2 In some more preferred embodiments, C and D satisfy the following: 0.58≦C / D 2 In some embodiments, C / D 2The value of is 0.21, 0.25, 0.28, 0.34, 0.39, 0.43, 0.51, 0.57, 0.58, 0.59, 0.67, 0.73, 0.77, 0.79, 0.88, 0.89, 0.95, 0.96, 0.99, 1.09, 1.13, 1.17, 1.19, 1.2, or a range consisting of any two of these values. 2 By adjusting the value of within the above range, the trade-off relationship between the displaceable space of the conductive agent and the degree and speed of expansion and contraction of the silicon carbon composite particle volume can be further adjusted, and the high temperature cycle resistance increase rate and the fast charging cycle resistance increase rate can be further improved.

[0027] In some embodiments, D satisfies 7.1≦D≦10.9. In some embodiments, D satisfies 7.4≦D≦10.9. In some embodiments, D satisfies 7.1≦D≦9.2. In some embodiments, D satisfies 7.4≦D≦9.2. In some embodiments, D satisfies 7.5≦D≦9.2. In some embodiments, D satisfies 7.4≦D≦8.8. In some embodiments, D satisfies 7.5≦D≦8.8. In some embodiments, the value of D is 7.1, 7.3, 7.4, 7.5, 7.6, 7.8, 8.2, 8.4, 8.8, 9.0, 9.2, 9.4, 9.5, 9.9, 10.3, 10.5, 10.7, 10.9, or a value within a range consisting of any two of these values. By adjusting the value of D within the above range, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0028] In some embodiments, C satisfies 25 ≤ C ≤ 59. In some embodiments, C satisfies 25 ≤ C ≤ 54. In some embodiments, C satisfies 33 ≤ C ≤ 59. In some more preferred embodiments, C satisfies 33 ≤ C ≤ 54. In some more preferred embodiments, C satisfies 33 ≤ C ≤ 48. In some more preferred embodiments, C satisfies 45 ≤ C ≤ 54. In some more preferred embodiments, C satisfies 45 ≤ C ≤ 48. In some embodiments, C is a value within a range consisting of 25, 27, 28, 29, 30, 33, 36, 38, 39, 40, 43, 45, 46, 47, 48, 51, 54, 55, 59 or any two of these numerical values. By adjusting the value of C within the above range, the rapid charge cycle resistance increase rate and the high temperature cycle resistance increase rate of the secondary battery can be further improved.

[0029] In some embodiments, the silicon-carbon composite particles may include at least one of a silicon-based material, a silicon-carbon material (a composite of a silicon-based material and a carbon-based material), and a silicon oxide (SiO x , where 0 < x ≤ 2).

[0030] In some embodiments, the silicon-based material may be silicon particles, silicon alloy particles, etc.

[0031] For example, the composite of a silicon-based material and a carbon-based material may be an active material obtained by dispersing silicon nanoparticles having an average particle size of 200 nm or less on carbon-based material particles, and then coating the carbon (an active material in which silicon (Si) particles are present on and in graphite) or the like. The average particle size of the secondary particles of the composite of a silicon-based material and a carbon-based material may be 5 μm to 20 μm. In the present invention, the secondary particles of the composite of a silicon-based material and a carbon-based material are silicon-based material particles and / or carbon-based material particles in the composite of a silicon-based material and a carbon-based material, such as silicon nanoparticles. The average particle size of the silicon nanoparticles may be 5 nm or more, for example, 10 nm or more, for example, 20 nm or more, for example, 50 nm or more, for example, 70 nm or more. The average particle size of the silicon nanoparticles may be 200 nm or less, 150 nm or less, 100 nm or less, 50 nm or less, 20 nm or less, or 10 nm or less. For example, the average particle size of silicon nanoparticles may be 100 nm to 150 nm. The average particle size of secondary particles of a composite of a silicon-based substance and a carbon-based substance may be 5 μm to 20 μm, for example, 7 μm to 15 μm, for example, 10 μm to 13 μm.

[0032] In some preferred embodiments, the silicon carbon composite particles include a carbon skeleton and a protective layer located on at least a portion of the surface of the carbon skeleton, the material of the protective layer includes amorphous carbon, and the material of the carbon skeleton includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, and hard carbon. By using this type of silicon carbon composite particles, the rapid charge cycle resistance increase rate and high temperature cycle resistance increase rate of the secondary battery can be further improved.

[0033] In some embodiments, the ratio of the number of silicon carbon composite particles is 1% to 25% based on the total number of particles in the negative electrode mixture layer, for example, the ratio of the number of silicon carbon composite particles is 1%, 3%, 6%, 7%, 9%, 11%, 12%, 15%, 17%, 19%, 20%, 21%, 24%, 25%, or a value within a range consisting of any two of these values. By adjusting the ratio of the number of silicon carbon composite particles in the negative electrode mixture layer to within the above range, the rapid charge cycle resistance increase rate and high temperature cycle resistance increase rate of the secondary battery can be further improved.

[0034] Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, or the like.

[0035] In some embodiments, the negative electrode mixture layer includes a conductive agent, and the type of the conductive agent is not limited, and any known conductive material can be used. Examples of the conductive agent include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above conductive agents can be used alone or in any combination.

[0036] In some more preferred embodiments, the conductive agent comprises carbon nanotubes, and the use of a conductive agent comprising carbon nanotubes can further improve the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery.

[0037] The present invention is not particularly limited to the negative electrode current collector, as long as the object of the present invention can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a polymer substrate coated with a conductive metal. Here, the conductive metal includes, but is not limited to, copper, nickel, or titanium, and the material of the polymer substrate includes, but is not limited to, at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate, and p-phenylene terephthalamide. In the present invention, the thickness of the negative electrode current collector and the negative electrode mixture layer is not particularly limited, as long as the object of the present invention can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the negative electrode mixture layer on one side is 30 μm to 160 μm. In the present invention, the negative electrode mixture layer may be provided on one surface in the thickness direction of the negative electrode current collector, or may be provided on both surfaces in the thickness direction of the negative electrode current collector. Here, the "surface" may be the entire area of ​​the negative electrode current collector, or a part of the area of ​​the negative electrode current collector, and is not particularly limited in the present invention as long as the object of the present invention can be achieved.

[0038] The negative electrode mixture layer may further include a negative electrode binder. The negative electrode binder can enhance the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of the negative electrode binder is not particularly limited, and may be a material that is stable in the electrolyte or the solvent used in the manufacture of the electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of the resin binder include, but are not limited to, fluororesin, polyacrylonitrile (PAN), polyimide resin, acrylic acid resin, polyolefin resin, and the like. When the negative electrode mixture slurry is prepared using an aqueous solvent, the negative electrode binder includes, but is not limited to, hydroxyethyl carboxymethyl cellulose (HECMC) or a salt thereof, carboxymethyl cellulose (CMC) or a salt thereof, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or a salt thereof, polyacrylic acid ester, polyvinyl alcohol, and the like.

[0039] For example, the negative electrode can be manufactured by the following method: A negative electrode mixture slurry containing a negative electrode binder, silicon carbon composite particles, a conductive agent, etc. is applied to a negative electrode current collector, dried, and then rolled to form a negative electrode mixture layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.

[0040] The present invention is not particularly limited to the compression density of the negative electrode pieces, as long as the object of the present invention can be achieved. For example, the compression density of the negative electrode pieces is 1.0 g / cm 3 ~1.85g / cm 3 The present invention is not particularly limited to the pressure for cold rolling the negative electrode pieces, as long as the object of the present invention can be achieved. For example, the pressure for cold rolling the negative electrode pieces may be 3 tons to 30 tons.

[0041] electrolyte The electrolyte used in the secondary battery according to the present invention includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte includes propylene carbonate and ethylene carbonate, and when the total mass percentage of the propylene carbonate and the ethylene carbonate is H% based on the mass of the electrolyte, H satisfies 15≦H≦50. In some embodiments, H satisfies 18≦H≦44. In some embodiments, H satisfies 18≦H≦39. In some embodiments, H satisfies 24≦H≦44. In some embodiments, H satisfies 24≦H≦39. In some embodiments, H satisfies 18≦H≦24. In some embodiments, H satisfies 39≦H≦44. In some embodiments, H is 15, 18, 19, 22, 23, 25, 28, 30, 32, 33, 36, 37, 39, 40, 43, 44, 50, or a value within a range consisting of any two of these values. By adjusting the value of H within the above range, the thickness and composition of the SEI film can be adjusted to reduce the possibility of interruption of the conductive network inside the negative electrode, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0042] In some embodiments, the electrolyte includes propyl propionate and ethyl propionate, and when the sum of the mass percentages of the propyl propionate and the ethyl propionate is L % based on the mass of the electrolyte, L satisfies 12≦L≦39. In some embodiments, L satisfies 12≦L≦34. In some embodiments, L satisfies 18≦L≦39. In some embodiments, L satisfies 18≦L≦34. In some embodiments, L satisfies 12≦L≦18. In some embodiments, L satisfies 34≦L≦39. In some embodiments, L is 12, 13, 16, 18, 19, 21, 24, 26, 27, 30, 32, 34, 36, 38, 39, or a value within a range consisting of any two of these values. By adjusting the value of L within the above range, the components and thickness of the SEI film can be improved, the connection between the silicon carbon composite particles and the conductive agent can be strengthened, and the high temperature cycle resistance increase rate and the fast charging cycle resistance increase rate of the secondary battery can be further improved.

[0043] In some embodiments, when the mass percentage of propyl propionate is L1% and the mass percentage of ethyl propionate is L2%, L1 and L2 satisfy 1.3≦L1 / L2≦2.8. In some embodiments, L1 and L2 satisfy 1.3≦L1 / L2≦2.3. In some embodiments, L1 and L2 satisfy 1.7≦L1 / L2≦2.8. In some embodiments, L1 and L2 satisfy 1.7≦L1 / L2≦2.3. In some embodiments, L1 and L2 satisfy 1.3≦L1 / L2≦1.7. In some embodiments, L1 and L2 satisfy 2.3≦L1 / L2≦2.8. In some embodiments, the value of L1 / L2 is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, or a value within a range consisting of any two of these values. By controlling the value of L1 / L2 within the above range, the uniformity of the SEI film can be improved, and the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved.

[0044] In some embodiments, L1 satisfies 4≦L1≦24. In some embodiments, L1 satisfies 8≦L1≦15. In some embodiments, L1 satisfies 10≦L1≦19. In some embodiments, L1 satisfies 13≦L1≦23. Illustratively, the value of L1 is 4, 5, 7, 8, 10, 11, 13, 15, 16, 18, 19, 20, 21, 23, 24, or a value within a range consisting of any two of these values. In the present invention, by controlling the value of L1 within the above range, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved.

[0045] In some embodiments, L2 satisfies 5≦L2≦22. In some embodiments, L2 satisfies 7≦L2≦15. In some embodiments, L2 satisfies 11≦L2≦18. In some embodiments, L2 satisfies 16≦L2≦21. Illustratively, the value of L2 is 4, 5, 7, 9, 10, 11, 12, 13, 15, 16, 18, 19, 20, 21, 22, or a value within a range consisting of any two of these values. In the present invention, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved by controlling the value of L2 within the above range.

[0046] In some embodiments, when the mass percentage of propylene carbonate is H1% and the mass percentage of ethylene carbonate is H2%, H1 and H2 satisfy 0.9≦H1 / H2≦2.3. In some embodiments, H1 and H2 satisfy 0.9≦H1 / H2≦2.0. In some embodiments, H1 and H2 satisfy 1.1≦H1 / H2≦2.3. In some embodiments, H1 and H2 satisfy 1.1≦H1 / H2≦2.0. In some embodiments, the value of H1 / H2 is 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.1, 2.2, 2.3, or a value within a range consisting of any two of these values. By adjusting the value of H1 / H2 within the above range, the uniformity of the SEI film can be further improved, and the secondary battery can achieve a lower high-temperature cycle resistance increase rate and a lower fast-charge cycle resistance increase rate.

[0047] In some embodiments, H1 satisfies 6≦H1≦30. In some embodiments, H1 satisfies 8≦H1≦19. In some embodiments, H1 satisfies 15≦H1≦23. In some embodiments, H1 satisfies 20≦H1≦29. Illustratively, the value of H1 is 6, 7, 8, 10, 11, 13, 15, 16, 18, 19, 20, 21, 23, 24, 25, 26, 27, 28, 29, 30, or a value within a range consisting of any two of these values. The present invention can further improve the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery by controlling the value of H1 within the above range.

[0048] In some embodiments, H2 satisfies 5≦H2≦29. In some embodiments, H2 satisfies 11≦H2≦19. In some embodiments, H2 satisfies 15≦H2≦23. In some embodiments, H2 satisfies 18≦H2≦27. Illustratively, the value of H2 is 5, 7, 9, 10, 11, 12, 13, 15, 16, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or a value within a range consisting of any two of these values. The present invention can further improve the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery by controlling the value of H2 within the above range.

[0049] In some embodiments, the electrolyte contains 1,3-propane sultone, and P satisfies 2.6≦P≦4.7, where P% is the mass percentage of 1,3-propane sultone based on the mass of the electrolyte. In some embodiments, P satisfies 2.6≦P≦4.2. In some embodiments, P satisfies 3.1≦P≦4.7. In some embodiments, P satisfies 3.1≦P≦4.2. In some embodiments, P satisfies 2.6≦P≦3.1. In some embodiments, P satisfies 4.2≦P≦4.7. In some embodiments, P is 2.6, 2.7, 2.8, 3.0, 3.2, 3.4, 3.5, 3.7, 3.8, 4.0, 4.2, 4.3, 4.4, 4.6, 4.7, or a value within a range consisting of any two of these values. By controlling the value of P within the above range, the elasticity of the solid electrolyte interface film and its ability to connect the conductive agent can be improved, and the high-temperature cycle resistance increase rate and the rapid charging cycle resistance increase rate can be further improved.

[0050] In some embodiments, the electrolyte includes at least one of fluorobenzene, fluoroethylene carbonate, and lithium difluorophosphate, and F1 satisfies 1.1≦F1≦4.3, where F1 is a mass percentage of fluorobenzene based on the mass of the electrolyte. In some embodiments, F1 satisfies 1.1≦F1≦3.7. In some embodiments, F1 satisfies 2.3≦F1≦4.3. In some embodiments, F1 satisfies 2.3≦F1≦3.7. In some embodiments, F1 satisfies 1.1≦F1≦2.3. In some embodiments, F1 satisfies 3.7≦F1≦4.3. In some embodiments, the value of F1 is 1.1, 1.3, 1.4, 1.8, 2.1, 2.2, 2.4, 2.6, 2.9, 3.2, 3.4, 3.6, 4.0, 4.2, 4.3, or a value within a range consisting of any two of these values. By adjusting the value of F1 within the above range, the present invention can further reduce the possibility of the conductive network inside the negative electrode being blocked, and the secondary battery can achieve a lower high-temperature cycle resistance increase rate and a lower fast charge cycle resistance increase rate.

[0051] In some embodiments, C and F1 are such that 3.4≦C / F1 2 In some embodiments, C and F1 satisfy the following: 3.4≦C / F1 2 In some embodiments, C and F1 satisfy the following: 5.5≦C / F1 2 In some embodiments, C and F1 satisfy the following: 5.5≦C / F1 2 In some embodiments, C and F1 satisfy the following: 7.0≦C / F1 2 In some embodiments, C and F1 satisfy the following: 3.4≦C / F1 2 In some embodiments, C / F1 2 The value of C / F1 is 3.4, 4.2, 4.8, 5.6, 6.0, 7.1, 7.9, 8.3, 9.5, 10.5, 11.2, 11.6, 12.8, 13.5, 13.8, or a value within a range consisting of any two of these values.2 By controlling the value of within the above range, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved.

[0052] In some embodiments, when the mass percentage of fluoroethylene carbonate is F2% based on the mass of the electrolyte, F2 satisfies 10.3≦F2≦19.8. In some embodiments, F2 satisfies 10.3≦F2≦18.7. In some embodiments, F2 satisfies 14.4≦F2≦19.8. In some embodiments, F2 satisfies 14.4≦F2≦18.7. In some embodiments, the value of F2 is 10.3, 12.8, 13.0, 13.8, 14.4, 14.7, 15.4, 16.1, 16.5, 17.1, 17.8, 18.5, 19.0, 19.4, 19.8, or a value within a range consisting of any two of these values. By controlling the value of F2 within the above range, the present invention can further reduce the possibility of interruption of the conductive network inside the negative electrode, and enable the secondary battery to achieve a lower high-temperature cycle resistance increase rate and a lower fast charge cycle resistance increase rate.

[0053] In some embodiments, when the mass percentage of lithium difluorophosphate is F3% based on the mass of the electrolyte, F3 satisfies 0.01≦F3≦0.32. In some embodiments, F3 satisfies 0.01≦F3≦0.22. In some embodiments, F3 satisfies 0.12≦F3≦0.32. In some embodiments, F3 satisfies 0.12≦F3≦0.22. In some embodiments, F3 satisfies 0.01≦F3≦0.12. In some embodiments, F3 satisfies 0.22≦F3≦0.32. In some embodiments, the value of F3 is 0.01, 0.02, 0.05, 0.07, 0.08, 0.12, 0.15, 0.16, 0.20, 0.22, 0.23, 0.25, 0.29, 0.31, 0.32, or a value within a range consisting of any two of these values. By controlling the value of F3 within the above range, the present invention can further reduce the possibility of interruption of the conductive network inside the negative electrode, and the secondary battery can achieve a lower high-temperature cycle resistance increase rate and a lower fast charge cycle resistance increase rate.

[0054] In some embodiments, the electrolyte contains dimethyl sulfone, and when the mass percentage of dimethyl sulfone is S% based on the mass of the electrolyte, S satisfies 1.1≦S≦3.4. In some embodiments, S satisfies 1.1≦S≦2.7. In some embodiments, S satisfies 2.7≦S≦3.4. In some embodiments, S is 1.1, 1.2, 1.4, 1.5, 1.7, 1.8, 1.9, 2.2, 2.5, 2.6, 2.7, 2.9, 3.1, 3.4, or a value within a range consisting of any two of these values. By controlling S within the above range, the possibility of irreversible displacement occurring in the process of the volume expansion and contraction of the silicon carbon composite particles of the conductive agent can be reduced, and the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved.

[0055] In some embodiments, the electrolyte contains 1,4-dioxane, and W satisfies 2.3≦W≦4.6, where W% is the mass percentage of 1,4-dioxane based on the mass of the electrolyte. In some embodiments, W satisfies 2.3≦W≦3.2. In some embodiments, W satisfies 3.2≦W≦4.6. In some embodiments, W is 2.3, 2.6, 2.7, 2.9, 3.0, 3.3, 3.4, 3.6, 3.7, 3.9, 4.2, 4.3, 4.5, 4.6, or a value within a range consisting of any two of these values. By controlling the value of W within the above range, the present invention can strengthen the connection strength between the silicon carbon composite particles and the conductive agent, and further improve the high temperature cycle resistance increase rate and the fast charge cycle resistance increase rate.

[0056] The type of the non-aqueous solvent of the present invention is not particularly limited, and may include at least one of a carbonate ester compound, a carboxylate compound, an ether compound, and other organic solvents as long as the object of the present invention can be achieved, but is not limited thereto. The carbonate ester compound may include at least one of a chain carbonate ester compound and a cyclic carbonate ester compound, but is not limited thereto. The chain carbonate ester compound may include at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, and methylethyl carbonate, but is not limited thereto. The cyclic carbonate ester compound may include at least one of ethylene carbonate, propylene carbonate, but is not limited thereto. The carboxylate ester compound may include at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone, and prolactone, but is not limited thereto. The ether compounds may include, but are not limited to, at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran. The other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, and trioctyl phosphate.

[0057] In some embodiments, the electrolyte is not particularly limited, and any known electrolyte can be used. The weight of the electrolyte is not particularly limited as long as it does not impair the effects of the present application.

[0058] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode mixture layer provided on the surface of the positive electrode current collector.

[0059] The positive electrode mixture layer includes a positive electrode active material, and the positive electrode mixture layer may be one layer or multiple layers. Each layer in the multiple layers of the positive electrode active material may include the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly absorb and release alkali metal ions.

[0060] The positive electrode active material includes a lithium transition metal oxide containing nickel and other transition metals, in which the amount of nickel relative to the total moles of transition metals is 60 mol% or more, such as 75 mol% or more, such as 80 mol% or more, such as 85 mol% or more, or for example 90 mol% or more.

[0061] For example, the lithium transition metal oxide may be a compound represented by the following formula α: [ka] In formula α, 0.9 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0.6 ≦ x < 1, 0 < y ≦ 0.3, 0 < z ≦ 0.3, and x + y + z = 1, M is at least one selected from the group consisting of manganese (Mn), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), and boron (B), and A is F, S, Cl, Br, or a combination thereof. For example, the above subscripts are 0.7 ≦ x < 1, 0 < y ≦ 0.3, and 0 < z ≦ 0.3; 0.8 ≦ x < 1, 0 < y ≦ 0.3, and 0 < z ≦ 0.3; 0.8 ≦ x < 1, 0 < y ≦ 0.2, and 0 < z ≦ 0.2; 0.83 ≦ x < 0.97, 0 < y ≦ 0.15, and 0 < z ≦ 0.15; or 0.85 ≦ x < 0.95, 0 < y ≦ 0.1, and 0 < z ≦ 0.1.

[0062] For example, the lithium transition metal oxide is at least one of the compounds represented by the following formula β and formula γ.

Chemical formula

Chemical formula

[0063] In formula γ, 0.6 ≦ x ≦ 0.95, 0 < y ≦ 0.2, and 0 < z ≦ 0.1. For example, 0.7 ≦ x ≦ 0.95, 0 < y ≦ 0.3, and 0 < z ≦ 0.3. For example, 0.8 ≦ x ≦ 0.95, 0 < y ≦ 0.3, and 0 < z ≦ 0.3. For example, 0.82 ≦ x ≦ 0.95, 0 < y ≦ 0.15, and 0 < z ≦ 0.15. For example, 0.85 ≦ x ≦ 0.95, 0 < y ≦ 0.1, and 0 < z ≦ 0.1.

[0064] For example, the lithium transition metal oxide is LiNi 0.6 Co0.2 Mn 0.2 O2, LiNi 0.88 Co 0.08 Mn 0.04 O2, LiNi 0.8 Co 0.15 Mn 0.05 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi0.88Co0.1Mn 0.02 O2, LiNi 0.8 Co 0.15 Al 0.05 O2 or LiNi 0.88 Co 0.1 Al 0.02 It may be O2.

[0065] According to another embodiment, the positive electrode active material comprises at least one active material selected from the group consisting of Li-Ni-Co-Al (NCA), Li-Ni-Co-Mn (NCM), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), and lithium iron phosphate (LiFePO4).

[0066] In some embodiments, the positive electrode mixture layer includes a positive electrode conductive material, and the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of the positive electrode conductive material may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials can be used alone or in any combination.

[0067] The type of positive electrode binder used in the manufacture of the positive electrode mixture layer is not particularly limited, and in the case of the coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode may be used. Examples of positive electrode binders include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenated products, ethylene-propylene-diene terpolymers (EPDM), styrene-ethylene-butadiene-ethylene copolymers, and styrene-isoprene rubber. The positive electrode binder may include, but is not limited to, one or more of the following: thermoplastic elastomer-like polymers such as styrene block copolymers or hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; ion-conductive polymer compositions having alkali metal ions (especially lithium ions), etc. The positive electrode binder may be used alone or in any combination.

[0068] The type of solvent for forming the positive electrode slurry is not limited, and may be any solvent capable of dissolving or dispersing the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as required. Examples of the solvent for forming the positive electrode slurry may include any one of an aqueous solvent and an organic solvent. Examples of the aqueous medium may include, but are not limited to, a mixed medium of alcohol and water, water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphoramide and dimethylsulfoxide.

[0069] A thickener is usually used to adjust the viscosity of the slurry. When using an aqueous medium, a thickener and a styrene butadiene rubber (SBR) emulsion are used to form a slurry. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners can be used alone or in any combination.

[0070] The type of the positive electrode current collector is not particularly limited, and may be any of the known materials suitable for use as a positive electrode current collector. Examples of the positive electrode current collector may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating layer, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0071] In order to reduce the electrical contact resistance between the positive electrode current collector and the positive electrode mixture layer, the surface of the positive electrode current collector may include a conductive assistant or a conductive coating layer. Examples of the conductive assistant may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of the conductive coating layer may include a mixture layer containing an inorganic oxide, a conductive agent, and an adhesive.

[0072] The positive electrode can be produced by forming a positive electrode mixture layer containing a positive electrode active material and an adhesive on a current collector. The positive electrode using the positive electrode active material can be produced by a conventional method such as mixing the positive electrode active material and the adhesive, and optionally a conductive material and a thickener, by dry mixing, forming a sheet, and pressing the sheet to a positive electrode current collector, or dissolving or dispersing these materials in a liquid medium to form a slurry, applying the slurry to a positive electrode current collector, and drying to form a positive electrode mixture layer on the current collector.

[0073] Separator In order to prevent short circuits, a separator is usually provided between the positive electrode and the negative electrode, and in this case, the electrolyte of the present invention is usually used by permeating this separator.

[0074] The material and shape of the separator are not particularly limited as long as they do not significantly impair the effects of the present invention. The separator may be a resin, glass fiber, inorganic material, etc., made of a material stable to the electrolyte of the present invention. In some embodiments, the separator includes a porous sheet or nonwoven fabric-like material with excellent liquid retention. Examples of materials for the resin or glass fiber separator may include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The above separator materials may be used alone or in any combination.

[0075] The separator may be formed by laminating the above-mentioned materials, and examples thereof may include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0076] Examples of inorganic materials may include, but are not limited to, oxides such as alumina, silica, etc.; nitrides such as aluminum nitride, silicon nitride, etc.; sulfates (e.g., barium sulfate, calcium sulfate, etc.). The form of the inorganic material may include, but is not limited to, particulate or fibrous.

[0077] The separator may be in the form of a film, examples of which include, but are not limited to, nonwoven fabric, woven fabric, microporous film, etc. In the form of a film, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent film-like separator, the following separators can also be used. That is, a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or negative electrode by using a resin-based binder, for example, a separator formed by forming a porous layer on both sides of the positive electrode using alumina particles with a 90% particle size of less than 1 μm using a fluororesin as a binder can also be used.

[0078] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is more than 1 μm, more than 5 μm, or more than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, the insulating properties and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0079] The present invention further provides an electronic device including a secondary battery according to the present invention.

[0080] The use of the secondary battery according to the present invention is not particularly limited, and may be used in any electronic device known in the prior art. In some embodiments, the secondary battery according to the present invention may be used in, but is not limited to, laptops, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, liquid crystal televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, auxiliary bicycles, bicycles, lighting equipment, toys, game machines, watches, power tools, photo flashes, cameras, large household storage batteries, and lithium ion capacitors. EXAMPLES

[0081] Hereinafter, the embodiment of the secondary battery of the present invention will be described in more detail with reference to examples and comparative examples using a lithium ion battery as an example. Those skilled in the art should understand that the preparation methods described in the present invention are merely exemplary, and any other suitable preparation methods are within the scope of the present invention. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0082] Measurement method Resistance increase rate after high temperature (45℃) cycle (1) Measurement of initial resistance: After placing the lithium-ion battery in a charger / discharger at room temperature (25°C), it was charged at a constant current of 0.33C to 4.45V, then charged at a constant voltage of 4.45V, and the charging was stopped when the current dropped to 0.05C. It was discharged at a constant current of 0.33C to 3.0V. Then, after charging and discharging three times each according to the above charge / discharge process, the battery was set to SOC 50% based on the final discharge capacity. Then, the DC internal resistance (PNE-0506, charger / discharger) was measured by the voltage drop when a discharge pulse was applied at 5A (2.5C) for 10 seconds, and the resistance at this time was defined as the initial resistance.

[0083] (2) High-temperature cycle: The lithium-ion battery whose initial resistance had been measured was transferred to a high temperature (45°C), and then the above-mentioned charge and discharge process was counted as one cycle, and a total of 200 charge and discharge cycles were performed.

[0084] (3) Resistance after high-temperature cycles: After transferring the lithium-ion battery to a charge-discharge device at room temperature, the SOC was set to 50%, and the resistance after 200 cycles was measured by the voltage drop when a discharge pulse of 5A (2.5C) was applied for 10 seconds using a PNE-0506 charge-discharge device.

[0085] (4) The resistance increase rate R1 after high-temperature (45°C) cycling was calculated.

number

[0086] (2) Rapid charging cycle: The lithium-ion battery was charged at a constant current of 5C up to a voltage of 4.45V, then further charged at a constant voltage of 4.45V down to a current of 0.05C, left for 10 minutes, and then discharged at a constant current of 1C down to an off-state voltage of 3.0V. The above charging and discharging process constituted one cycle, and a total of 200 charging and discharging cycles were performed.

[0087] (3) Resistance after rapid charge cycles: The SOC was set to 50%, and the resistance after 200 cycles was measured by measuring the voltage drop when a discharge pulse of 5A (2.5C) was applied for 10 seconds using a PNE-0506 charge / discharge device.

[0088] (4) The rapid charging (5C) cycle resistance increase rate R2 was calculated.

number

[0089] Mass percentage of silicon element (C) The negative electrode pieces were cut into pieces of 1 cm × 1 cm size, and then the cut surfaces of the negative electrode pieces were polished using argon plasma polishing (CP) technique to prepare CP samples.

[0090] Silicon carbon composite particles in the CP sample were selected and cut into sheets using focused ion beam (FIB) to obtain FIB samples.

[0091] Spectral analysis was performed on the cut surface of the FIB sample, specifically, a randomly selected area of ​​1 μm × 1 μm was scanned in the center of the silicon carbon composite particle to measure the mass percentage (wt%) of silicon and carbon elements, and the mass percentage of silicon was calculated. The center of the silicon carbon composite particle is the area larger than 1 μm from the surface of the silicon carbon composite particle.

[0092] Average particle size of silicon carbon composite particles (D) The negative electrode pieces were cut into pieces of 1 cm × 1 cm size, and then the cut surfaces of the negative electrode pieces were polished using argon plasma polishing (CP) technology to prepare CP samples.

[0093] Select a silicon carbon composite particle in the CP sample, and record the cross-sectional area of ​​the silicon carbon composite particle as S, where S = π × R. 2 R was calculated by the following formula. The particle size of the silicon carbon composite particles was set to 2R.

[0094] A total of 20 silicon carbon composite particles were randomly selected, and the arithmetic mean of the particle sizes of the 20 silicon carbon composite particles was calculated and recorded as the average particle size D of the silicon carbon composite particles.

[0095] Example 1-1 <Preparation of negative electrode> Preparation of silicon carbon composite particles: The carbon precursor resin carbon was placed in a rotary furnace, and a mixture of silane and argon gas was passed through it. The deposition was carried out for 6.5 hours at a deposition temperature of 550°C to obtain silicon carbon composite particles. The volume ratio of silane to argon gas was 3:7.

[0096] Preparation of negative electrode pieces: Silicon carbon composite particles and artificial graphite were uniformly mixed in a mass ratio of 12:88 to obtain the negative electrode active material. The above negative electrode active material, styrene butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water was added as a solvent and stirred uniformly to obtain a negative electrode slurry with a solid content of 45 Wt%. The negative electrode slurry was uniformly coated on one surface of a negative electrode current collector copper foil with a thickness of 6 μm and dried to obtain a negative electrode piece coated with a negative electrode mixture layer on one side. The above steps were repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode piece coated with a negative electrode mixture layer on both sides. The negative electrode piece was cold-rolled, cut, slit, and dried to obtain a negative electrode piece with a specification of 76.6 mm x 875 mm.

[0097] <Preparation of positive electrode> The positive electrode active material lithium cobalt oxide, the conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) was added, and the mixture was uniformly stirred with a vacuum stirrer to obtain a positive electrode slurry with a solid content of 70 Wt%. The positive electrode slurry was uniformly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9 μm and dried to obtain a positive electrode piece coated with a positive electrode mixture layer on one side. The above steps were repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode piece coated with a positive electrode mixture layer on both sides. The positive electrode piece was cold-rolled, cut, slit, and dried to obtain a positive electrode piece with a specification of 74 mm x 867 mm.

[0098] <Preparation of electrolyte> Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solution containing propyl propionate, ethyl propionate, ethylene carbonate, propylene carbonate, and diethyl carbonate (DEC) in a glove box with a dry argon atmosphere. Based on the mass of the electrolyte, the mass percentage of LiPF6 was set to 12.5%, and the mass percentages of other substances were as shown in Table 1: the mass percentage of propyl propionate was L1%, the mass percentage of ethyl propionate was L2%, the mass percentage of propylene carbonate was H1%, the mass percentage of ethylene carbonate was H2%, and the remaining amount was DEC.

[0099] <separator> As the separator, a 15 μm-thick porous polyethylene film (provided by Celgard) was used.

[0100] <Preparation of lithium-ion batteries> The positive and negative electrodes prepared as described above were connected to tabs. They were then stacked with a separator between them to obtain a laminate. The laminate was then housed in an aluminum laminate case together with an electrolyte. The opening of the case was heat sealed, and a lithium-ion battery was produced through steps such as chemical conversion and degassing.

[0101] Examples 1-2 to 1-31, Comparative Examples 1 to 3 The same as Example 1-1 was performed except that the parameters were adjusted according to Table 1. By adjusting the deposition time when producing the silicon carbon composite particles, the mass percentage C% of the silicon element was set as shown in Table 1. By crushing and ball milling the silicon-based particles, the average particle diameter D μm of the silicon-based particles was set as shown in Table 1. The negative electrode mixture layer of Comparative Example 3 did not contain silicon carbon composite particles, and the negative electrode active material was artificial graphite particles.

[0102] [Table 1]

[0103] As can be seen from Table 1, the secondary battery according to the present invention has an average particle diameter D μm of the silicon carbon composite particles and a C value in the mass percentage C % of silicon element of 0.21≦C / D 2 By controlling the ratio C / D to ≦1.2, the trade-off relationship between the degree and speed of expansion and contraction of the displaceable space of the conductive agent and the volume of the silicon carbon composite particles can be adjusted, thereby achieving a high energy density in the secondary battery while simultaneously improving the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate. 2 The value of C / D is 0.39 or less. 2 By adjusting the C / D ratio to satisfy ≦0.96, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved. 2 The value of C / D is 0.58 or less. 2 ≦0.88, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further significantly improved. In particular, by adjusting the values ​​of D and / or C to satisfy 7.1≦D≦10.9 and / or 25≦C≦59, respectively, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further improved.

[0104] In particular, by controlling the H value in the total mass percentage H% of propylene carbonate and ethylene carbonate in the electrolyte to satisfy 15≦H≦50, and combining with the average particle size of the silicon carbon composite particles and the mass percentage of silicon element in the negative electrode, a remarkable improvement effect can be exhibited in the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery. In particular, by controlling the L value in the total mass percentage L% of propyl propionate and ethyl propionate in the electrolyte to satisfy 12≦L≦39 and / or controlling the H value in the total mass percentage H% of propylene carbonate and ethylene carbonate in the electrolyte to satisfy 18≦H≦44, the thickness and composition of the SEI film can be adjusted, and when combined with silicon-based composite particles and a conductive agent, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved. In particular, by controlling the value of L to fall within the range of 18≦L≦34 and / or controlling the value of H to satisfy 24≦H≦39, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further significantly improved.

[0105] In particular, by adjusting the L1 / L2 value to satisfy 1.3≦L1 / L2≦2.8 when the mass percentage of propyl propionate L1% and the mass percentage of ethyl propionate L2% in the electrolyte, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved. Furthermore, by adjusting the H1 / H2 value to satisfy 0.9≦H1 / H2≦2.3 when the mass percentage of propylene carbonate H1% and the mass percentage of ethylene carbonate H2% in the electrolyte, the secondary battery can achieve a lower high-temperature cycle resistance increase rate and rapid charge cycle resistance increase rate.

[0106] Examples 2-1 to 2-32 It was the same as Example 1-27, except that the content P% of 1,3-propane sultone, the content F1% of fluorobenzene, the content F2% of fluoroethylene carbonate, the content F3% of lithium difluorophosphate and / or the content S% of dimethyl sulfone were adjusted according to the parameters in Table 2. The content of DEC was adjusted according to the contents of the above components.

[0107] [Table 2]

[0108] As can be seen from Table 2, the present invention can further improve the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate by further controlling the value of P in the mass percentage P% of 1,3-propane sultone in the electrolyte to satisfy 2.6≦P≦4.7, and furthermore, by controlling the value of P to satisfy 3.1≦P≦4.2, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be further significantly reduced.

[0109] In particular, the present invention allows the secondary battery to achieve a lower high-temperature cycle resistance increase rate and a lower rapid charge cycle resistance increase rate by controlling the F1 value in the mass percentage F1% of fluorobenzene in the electrolyte to satisfy 1.1≦F1≦4.3. Furthermore, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be improved more significantly by controlling the F2 value in the mass percentage F2% of fluoroethylene carbonate in the electrolyte to satisfy 10.3≦F2≦19.8. In particular, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved by controlling the F2 value in the mass percentage F3% of lithium difluorophosphate in the electrolyte to satisfy 0.01≦F3≦0.32.

[0110] In particular, the present invention can further improve the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate by controlling the S value in the mass percentage S% of dimethyl sulfone in the electrolyte to satisfy 1.1≦S≦3.4. In particular, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved by controlling the W value in the mass percentage W% of 1,4-dioxane in the electrolyte to satisfy 2.3≦W≦4.6. In particular, when dimethyl sulfone and 1,4-dioxane are simultaneously blended in the electrolyte, the high-temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be more significantly reduced.

[0111] Examples 3-1 to 3-6 It was the same as Example 1-27, except that the parameters of the fluorobenzene content F1% and the silicon element content C% were adjusted according to Table 3. The content of DEC was adjusted according to the content of fluorobenzene.

[0112] [Table 3]

[0113] From Table 3, C / F1 2 The value of C / F1 is 3.4 or less. 2 It can be seen that the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate can be further improved by adjusting the C / F1 2 The value of C / F1 is 5.5 or less. 2 By controlling the ratio so as to satisfy the condition of ≦7.0, the high temperature cycle resistance increase rate and the rapid charge cycle resistance increase rate of the secondary battery can be improved more significantly.

[0114] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the principles and scope of the invention.

Claims

1. A secondary battery including a positive electrode, a negative electrode, and an electrolyte, the negative electrode includes a current collector and a negative electrode mixture layer provided on at least one surface of the current collector, the negative electrode mixture layer contains silicon carbon composite particles and a conductive agent, The silicon carbon composite particles have an average particle size of D μm; The silicon-carbon composite particles contain silicon and carbon, and when the mass percentage of the silicon element is C% based on the total mass of the silicon element and the carbon element, C and D satisfy the following relationship: 0.21≦C / D 2 ≦1.2 is satisfied, the electrolyte comprises propylene carbonate and ethylene carbonate; A secondary battery, wherein when a total mass percentage of the propylene carbonate and the ethylene carbonate is H % based on the mass of the electrolyte solution, H satisfies 15≦H≦50.

2. The C and D are 0.39≦C / D 2 2. The secondary battery according to claim 1, wherein the above satisfies ≦0.

96.

3. The D satisfies 7.1≦D≦10.9, and the C satisfies 25≦C≦59, and / or The C and D are 0.58≦C / D 2 2. The secondary battery according to claim 1, wherein the relationship satisfies ≦0.

88.

4. the electrolyte further comprises propyl propionate and ethyl propionate; 2. The secondary battery according to claim 1, wherein, when a total mass percentage of the propyl propionate and the ethyl propionate is L % based on a mass of the electrolyte solution, L satisfies 12≦L≦39 and H satisfies 18≦H≦44.

5. The electrolyte solution is (1) 18≦L≦34; and (2) 24≦H≦39; The secondary battery according to claim 4 , wherein at least one of the above conditions is satisfied.

6. Based on the mass of the electrolyte, the electrolyte is (1) The mass percentage of the propyl propionate is L 1 %, and the mass percentage of the ethyl propionate is L 2 When set to %, L 1 and L 2 1.3≦L 1 / L 2 ≦2.8; and (2) The mass percentage of the propylene carbonate is H 1 %, and the mass percentage of the ethylene carbonate is H 2 When %, H 1 and H 2 0.9≦H 1 / H 2 ≦2.3 is satisfied, The secondary battery according to claim 4 , wherein at least one of the above conditions is satisfied.

7. Said L 1 and the L 2 1.7≦L 1 / L 2 ≦2.3, and / or The H 1 and the above H 2 1.1≦H 1 / H 2 The secondary battery according to claim 6 , wherein the above satisfies the condition ≦2.

0.

8. The electrolyte contains 1,3-propane sultone, 2. The secondary battery according to claim 1, wherein, when a mass percentage of the 1,3-propane sultone is defined as P % based on a mass of the electrolyte, P satisfies 2.6≦P≦4.

7.

9. The secondary battery according to claim 8 , wherein P satisfies 3.1≦P≦4.

2.

10. the electrolyte includes at least one of fluorobenzene, fluoroethylene carbonate, and lithium difluorophosphate; Based on the mass of the electrolyte, the electrolyte is (1) The mass percentage of the fluorobenzene is F 1 When set to %, F 1 1.1≦F 1 ≦4.3 is satisfied, (2) The mass percentage of the fluoroethylene carbonate is F 2 When set to %, F 2 , 3≦F 2 ≦19.8; and (3) The mass percentage of the lithium difluorophosphate is F 3 When set to %, F 3 0.01≦F 3 ≦0.32 is satisfied, The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

11. The electrolyte includes dimethyl sulfone, The secondary battery according to claim 1 , wherein, when a mass percentage of the dimethyl sulfone is S % based on a mass of the electrolyte, S satisfies 1.1≦S≦3.

4.

12. the electrolyte comprises 1,4-dioxane; 2. The secondary battery according to claim 1, wherein, when a mass percentage of the 1,4-dioxane is W % based on a mass of the electrolyte solution, W satisfies 2.3≦W≦4.

6.

13. The above C and the above F 1 3.4≦C / F 1 2 The secondary battery according to claim 10 , wherein the above satisfies ≦13.

8.

14. the silicon carbon composite particles include a carbon skeleton and a protective layer located on at least a portion of the carbon skeleton; the material of the protective layer includes amorphous carbon; 2. The secondary battery according to claim 1, wherein the carbon skeleton material comprises at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, and hard carbon.

15. The secondary battery according to claim 1 , wherein the conductive agent comprises carbon nanotubes.

16. An electronic device comprising the secondary battery according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN117393839A

  • Secondary battery and electronic device

    CN117996190A

  • Electrolytes, electrochemical devices and electronic devices

    JP2023510989A

  • Vehicle Braking Apparatus

    KR1020220170460A

  • Nonaqueous electrolyte secondary battery

    WO2019230908A1